Rejuvenation Through Ayurveda: A Way Towards Delaying Aging Process. - Garg, Nisha; Panda , Srikant Kumar (International Research Journal of Ayurveda & Yoga, 2021)
The process of rendering young again by causing beneficial changes in the human body comes under the rejuvenation therapy. Each and every individual surrounding us in the cosmos wants to be remain young as several changes comes under aging process which causes various alterations in biological, physiological, psychological, behavioural and social aspects. Finally, aging leads to the old age period in which most of the individuals become fully or partially dependent on others even for their daily activities. To achieve healthy lifestyle and for delaying the aging process without experiencing side effects, everyone wants some remarkable solution. Ayurveda plays a major role for standstill the aging process and having an immense scope in this context through its various modalities like Rasayana therapy which is very much helpful in replenishing the vital fluids of the body; boosting the Vyadhikshamatva Bala and thus keeping us away from various ailments and prevents against ill effects of aging process and advanced age. Withania somnifera (Ashwagandha), Emblica officinalis (Aamalaki) and Terminalia chebula (haritaki) are some examples of potential and revered ayurvedic rejuvenator. Ashwagandha promotes energy levels and also mitochondrial health by its anxiolytic effect and works as anti-inflammatory and anti-arthritic agent also. Aamla, also known to be as Indian gooseberry is a potential antioxidant, immune-modulatory herb and having Vaya-Sthaapna Gunas that is anti-aging properties. Aamla act as an influential rejuvenator by nourishing the dhatus (the body tissues) and gently detoxify the body by removing toxins from the body. Haritaki, also known as shiva is a powerful Rasayana, anti aging agent, a potent immune modulator and an effective antioxidant. Ritu haritaki is also a very useful concept of Ayurveda for rejuvenation. Rejuvenation through Ayurveda is a very important concept which should be keenly studied and applied.